Pengaruh Kepemilikan Negara Dan Asing Terhadap Corporate Risk Taking - Indah Kurniawati; Puput Tri Komalasari (Universitas Airlangga, 2014)
This study aimed to investigate the effect of state ownership and foreign ownership of corporate risk taking as well as the control variable return on assets (ROA) and the size of the companies that influence the corporate risk taking. The sample of this study was 181 companies from non-financial companies listed on the Indonesia Stock Exchange in 2010-2013. The analysis technique used is multiple linear regression analysis. The results obtained are state ownership significant negative effect on the corporate risk taking and foreign ownership is significant positive effect on corporate risk taking. In the control variable is return on assets (ROA) significant positive effect on corporate risk taking and the size of the company significant negative effect on corporate risk taking.